"Perfect match" of the carbazole-based conducting polymer and polyoxometalate nanocomposite components for enhanced optical and electrical properties. (15th March 2023) - Guzel, Merve; Torlak, Yasemin; Choi, Hyosung; Ak, Metin
Graphical abstract: Highlights: A perfect match of the carbazole-based CP and POM nanocomposite components was investigated. Molybdenum-based POM derivative has an extended effect on the polymer optical properties. Optical and electrical properties of the composite films have been compared with each other. Electrochromic device application of composite structure with extended optical properties has been performed. Abstract: Conducting polymers (CPs) have been recognized as ideal matrices for electroactive species because of their ability to host them at the molecular level and can interact synergistically. One of the promising approaches is to make the optical and electrical properties of CPs easily tunable with nano-sized reactive inorganic species such as electroactive molecules, metal oxides, and polyoxometalates. In this study, organic–inorganic nanocomposites that include a triazine-centered carbazole and different types of polyoxometalate (Keggin and Dawson) derivatives have been electrochemically synthesized to obtain enhanced electrical and optical properties by determining the perfect match of the components. In situ incorporating POM clusters into cross-linked conducting polymers lead to organic–inorganic hybrid materials with not only value-adding properties but also synergistic effects. It has been observed that charge density and optical contrast values increased with the introduction of POM derivatives into the conductive polymer structure, while these values decreased when the feed ratio of POM derivatives increased. Furthermore, the highest optical contrast and charge density values were obtained in the molybdenum (POM4) based POM derivative when compared to all POM derivatives. Within the scope of technological application, dual-type electrochromic devices (ECDs) have been fabricated using poly(3, 4-ethylenedioxythiophene) (PEDOT) and PCT3 or POM4/PCT3 and their characterization studies have been carried out.